Time, power and resistance: Guest editors introduction (Sociologisk Forskning, 2019)
Time, power and resistance are all central sociological concepts, but only rarely have the intertwi- ning between all three been explored. Here the guest editors of the special issue of Sociologisk Forskning called ”Time, power and resistance” introduce five empirical research articles. The articles all investigate time and temporality in relation to forms of power, ranging from discursive power to dominant norms and state power. The resistances vary from organised, collective resistance to subtle and discreet forms of everyday and constructive resistance. Additionally, the guest editors point towards future avenues of research in the area and show sociologically interesting links between the three concepts.
Keywords: time; power; resistance; introduction; future research